Makna Simbolis dalam Upacara Adat Perkawinan di Kecamatan Kampar Kiri Hulu Kabupaten Kampar - Alber, Alber; Febria, Rhani; Andriana, Mella (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
Humans are very closely related to culture, so that humans are called cultural beings. Culture itself consists of ideas, symbols, and values as a result of human actions. At this time, a complete ceremony with all its procedures is still used and preserved and becomes something sacred besides the marriage contract. However, it is rare for people to know the meaning and significance of the symbols of the series of wedding ceremonies. In fact, it is not uncommon to make the series of ceremonies a source of pride without knowing more about their meanings and without explaining their benefits. This study aims to determine the implementation (stages) and meaning contained in the symbols of traditional wedding ceremonies in Kampar Kiri Hulu District, Batu Sasak Village, Kampar Regency. The author conducted the research by conducting observations, interviews with traditional figures (ninik mamak), and literature studies. This research is descriptive-analytical with qualitative methods. The results of this study are that the traditional wedding ceremony in Batu Sasak Village consists of stages or processions of ulok-ulok, antagh tando, manunggu buek, manjolang sumondo, and manjolang mintuo. At these stages there are several symbols; these symbols are usually represented in the form of objects. The symbols contained in the traditional wedding ceremony include ceno, sirih, pinang, gambir, soda, and tobacco.